Site-specific atomic-scale characterisation of retained austenite in a strip cast TRIP steel. (1st August 2017) - Xiong, Z.P.; Saleh, A.A.; Marceau, R.K.W.; Taylor, A.S.; Stanford, N.E.; Kostryzhev, A.G.; Pereloma, E.V.
Abstract: Knowledge of carbon content in retained austenite (RA) with different neighbouring phases is essential to understand the chemical stability of RA, which is useful for microstructure tuning of transformation-induced plasticity (TRIP) steels. The present study investigates different morphologies and chemical compositions of RA by correlating electron backscattering diffraction, transmission electron microscopy and atom probe tomography. The effect of neighbouring phases, such as polygonal ferrite, bainitic ferrite lath, ferrite in granular bainite and carbides, on the carbon content in the RA is investigated. The results reveal that the film RA morphology does not always have a higher carbon content than the blocky RA; as coarse RA sometimes displays a higher carbon content than the fine RA films or islands depending on the neighbouring phases. The diffusion of carbon and manganese between austenite and ferrite in bainitic ferrite/granular bainite has been explained according to either diffusionless and/or diffusional mechanism of bainitic ferrite formation followed by tempering. Graphical abstract: Highlights: The effect of neighbouring phases on retained austenite (RA) features was investigated. A lower carbon content in fine/film RA compared to coarse/blocky RA was experimentally demonstrated. At least locally controlled diffusion of substitutional solutes across the RA/bainitic ferrite lath interface was suggested.